Me and the economy. Evaluation of the performance in a teacher economic education program for schoolchildren in 6th grade - Denegri, Marianela (2011)
The present research studied the change in teaching practices of Basic Education (Primary School) teachers, from their participation in a training program in Economic Education. The sample consisted in 14 teachers of Understanding of the Environment, Language and Communication, and Mathematics courses, to who were applied the Economic Literacy Test for Adults (TAE-A) (Gempp, Denegri, Catalan, Caripán, Hermosilla & Caprile, 2007) and the Pattern of Observation of Teaching Practices (Denegri, 2005). The results reveals an increase in literacy economic levels and significant differences in teaching practices of the teachers participants, results are discussed considering the bibliographic review.